CASE SERIES: DEEP SEDATION FOR PAEDATRIC PATIENTS WITH PERICARDIAL EFFUSION - Soenarto, Ratna Farida; Hidayat, Jefferson; Zaintama, Hendy Armanda (Bali Journal of Anesthesiology, 2017)
Background: Pericardial effusion is an abnormal fluid accumulation in the pericardial space that potentially compromises cardiovascular function, thus it needs a prompt treatment. Pericardial effusion evacuation in paediatrics can be done by subxyphoid pericardiotomy, which requires patientâs cooperation. General anaesthesia for paediatrics with pericardial effusion has been reported unfavourable. This case series reports safe anaesthesia procedures done for pericardiocentesis through both sedation and general anaesthesia. Case Presentations: Cases were taken from Cipto Mangunkusumo Hospital, Jakarta, Indonesia. 6 patients underwent sedation and 3 patients underwent general anaesthesia. Both groups used ketamine, midazolam and fentanyl. Sevoflurane was used as inhalation agent for maintenance. Blood pressure, heart rate, and SpO2 were recorded before and after pericardiocentesis. In both groups, there were no significant different between systolic and diastolic blood pressure, heart rate, and SpO2 before and after the procedure (p>0.05). Immobilization through sedation or general anaesthesia is required to perform an optimal pericardiotomy. Anaesthetic agents were chosen based on their minimal effects toward myocardial depression. Fluids balance before and after the procedure was crucial to prevent hemodynamic instability during effusion evacuation. Conclusion: Both sedation and general anaesthesia were safe for pericardiocentesis, with concern toward anaesthetic agents that were minimally depressive to myocardium, combined with opioid analgesics and other sedative agents, with balanced anaesthesia principle. Optimal intravenous fluid therapy with echocardiography monitoring is crucial. Sedation is more advantageous for patients requiring pericardiocentesis without preoperative preparation for general anaesthesia.